Diskursus Komunikasi Public Relations dalam Konten YouTube “Kehidupan Talitha Curtis” - Wattimena, Grace Heidy Jane Amanda (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
This study analyzes the discourse of public relations communication in the management of messages and impressions presented through the YouTube content "Kehidupan Talitha Curtis" ("The Life of Talitha Curtis"). Talitha Curtis is a public figure whose life story has been marked by controversy surrounding aspects of her heritage, upbringing, and personal attributes, leading to negative stigma. However, through a strategic public relations approach, the narrative of Talitha’s life in this content is carefully crafted to construct a positive image of her as a resilient and strong individual. The research employs critical discourse analysis, focusing on textual elements, discursive practices, and social context to explore how Talitha Curtis leverages public relations communication to reposition her image in the public eye. The findings reveal that the content integrates elements of personal storytelling with emotionally evocative visuals to foster audience engagement. Additionally, the narrative consistently highlights Talitha's personal transformation journey, which creates a positive psychological impact on viewers and reinforces her social capital, enabling her reacceptance in the celebrity world.This study contributes to understanding how message and impression management through digital media can serve as an effective tool for repositioning public figures' images, particularly in reconciling an image affected by past controversies.